Welfare reform in California : results of the 1998 all-county implementation survey - Ebener, Patricia A. (Patricia Anne), 1949- (Rand, 1999)
The California Work Opportunity and Responsibility to Kids (CalWORKs) program is California's response to the welfare reforms Congress set in motion in 1996. In late 1998, RAND conducted the first of three statewide surveys on CalWORKs implementation. Survey responses indicate that the counties have made significant administrative changes in welfare operations, in the structure and organization of their welfare departments and other agencies, in staffing, and in information systems. Many counties have completed planning activities and have fully operational program components. Most counties report no major implementation problems to date but anticipate problems in the future with cumulative lifetime limits and work requirements. A majority of counties agreed that environmental characteristics such as the job market, housing, and transportation have hindered implementation; interagency relationships, planning, and experience with welfare reform have facilitated it. Nearly all agree that special-needs child care and transportation are inadequate. Complete survey responses from the 58 counties are contained in a companion volume, MR-1052/1-CDSS.